A heuristic algorithm for yard crane dispatching in container terminals - Lee, Zhen Jie (2014)
In any optimization algorithm with NP-hard problems, embedded simulation in that area usually incur high computation costs. One of the example would be the Yard Crane (YC) dispatching in container terminals. As such, it is of importance to reduce the simulation cost in YC dispatching. In this report, there will be 3 approaches mentioned; the main objective of these approaches is to reduce the simulation cost in the optimization algorithm and also to achieve high accuracy compared to the original optimization algorithm. From the experimental results, it was found that out of these 3 approaches, only one of them achieve a much closer result, albeit all 3 of them are able to reduce the simulation cost. Reasons for the failure of the 2 approaches will be analyzed.